Use of cholesterol and soluble tumour markers CEA and syndecan-2 in pleural effusions in cases of inconclusive cytology. Issue 8 (26th April 2019) - Gulyas, Miklos; Fillinger, Janos; Kaposi, Andras D; Molnar, Miklos
Abstract : Aims: In order to improve diagnostics in pleural effusions, additional value of effusion cholesterol, carcinoembryonic antigen (CEA) and syndecan-2 assays to cytology was studied. Methods: Biomarkers were measured in effusion supernatants from 247 patients, of whom 126 had malignant pleural involvement, and their additional diagnostic efficacy to cytology was assessed. Results: Syndecan-2 measurement, although gave detectable concentrations in all effusions with highest median value in mesotheliomas, was non-discriminative between different pathological conditions. CEA concentrations exceeding 5 ng/mL cut-off point indicated carcinomas, regardless of pleural involvement, which gave a sensitivity of 62% and specificity of 100% for carcinoma. Cholesterol concentration over 1.21 mmol/L cut-off value indicated neoplastic pleural involvement with 99% sensitivity and 'merely' 69% specificity, the latter mainly due to raised levels being associated also with benign inflammatory effusions. Combined CEA and cholesterol determinations increased the sensitivity for diagnosing carcinomatosis from 70% with cytology alone to 84% and established the correct diagnosis in 16 of 31 carcinomatosis cases with inconclusive cytology. Cholesterol measurement alone, with elevated level, in combination with absence of substantial number of inflammatory cells in effusion sediment proved to be a magnificent marker for neoplastic pleural involvement with 99% efficacy, and recognised all 36 such cases with inconclusive cytology. Conclusions: Simultaneous measurement of CEA and cholesterol concentrations in effusion, or at least cholesterol alone, in combination with non-inflammatory fluid cytology, provides additional specific information about neoplastic pleural involvement, and can therefore be used as an adjunct to cytology, above all, in inconclusive cases.